1996
DOI: 10.1046/j.1365-2559.1996.d01-412.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the liver in non‐cirrhotic portal hypertension of unknown aetiology

Abstract: Non-cirrhotic, long-standing portal hypertension of unknown aetiology is being re-evaluated histopathologically and clinically. In this study, we examined 107 livers with this condition (92 wedge biopsy and 15 autopsy specimens) from five institutions in Japan. These cases were histologically categorized into four groups: idiopathic portal hypertension (66 cases), nodular regenerative hyperplasia (14 cases), partial nodular transformation (two cases), and incomplete septal cirrhosis (25 cases). These four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
134
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 8 publications
8
134
0
Order By: Relevance
“…phlebosclerosis, intimal thickening or smooth muscle hyperplasia around portal veins, and a reduction in portal veins luminal area. [4][5][6] The results of the morphological and morphometrical analyses in the present study also confirmed smooth muscle hyperplasia and reduced luminal area of the portal veins.…”
Section: Discussionsupporting
confidence: 79%
“…phlebosclerosis, intimal thickening or smooth muscle hyperplasia around portal veins, and a reduction in portal veins luminal area. [4][5][6] The results of the morphological and morphometrical analyses in the present study also confirmed smooth muscle hyperplasia and reduced luminal area of the portal veins.…”
Section: Discussionsupporting
confidence: 79%
“…Namely, IPH is thought to result from presinusoidal vasoconstriction, causing a reduction of perfusion pressure and a decrease in local shear stress. 31,32 By contrast, cirrhotic livers are likely to be exposed to an elevation of intrasinusoidal pressure accompanied by hyperhemodynamic states, [33][34][35][36] implicating an increase in regional shear stress in sinusoids. It is therefore possible to hypothesize that Kupffer cells serve as a putative sensor cell that detects local hemodynamic changes in sinusoids and thereby alter their heme-degrading ability through the HO-1 induction.…”
Section: Discussionmentioning
confidence: 99%
“…IPH was histopathologically diagnosed according to the criteria proposed by the Japanese Study Group of Intrahepatic Haemodynamic Alterations (12,28). Wedge liver biopsy specimens and peripheral blood samples were collected from each patient.…”
Section: Patientsmentioning
confidence: 99%
“…Accumulated evidence indicates that IPH is an entirely distinct disease from liver cirrhosis. Aetiopathogenically, IPH has been associated with chronic abdominal infection (9), abnormal T-cell activation by continuous antigen stimulation (10), immunological abnormalities initiated by HLA-DR antigen expression by the portal tract microvasculature (11,12), exposure to toxic substances or drugs (13), and blood coagulation abnormalities (14). However, the pathogenesis of IPH remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%